A REVIEW OF PERMO‐TRIASSIC RESERVOIR ROCKS IN THE ZAGROS AREA, SW IRAN: INFLUENCE OF THE QATAR‐FARS ARCH. (19th June 2013) - Esrafili‐Dizaji, B.; Rahimpour‐Bonab, H.
Abstract : Four "supergiant" and numerous giant gasfields have been discovered in the Zagros area of SW Iran. The gasfields are concentrated in the eastern part of the foldbelt, in Fars Province and the adjacent offshore, and produce from Permo‐Triassic carbonates equivalent to the Khuff Formation. The carbonates belong to the upper member of the Dalan Formation and the overlying Kangan Formation. Reservoir rock quality is strongly influenced by tectonic setting and depositional environment, and also by diagenesis. The highest quality reservoirs occur in oolitic shoal facies; fracturing (especially in onshore fields) and dolomitisation (in offshore fields) have also influenced reservoir quality. Anhydrite plugging is common in reservoirs in offshore fields, while calcite cementation is dominant in onshore reservoirs. Facies variations in the Dalan‐Kangan Formations appear to correspond to syndepositional palaeohighs and depocentres. In the Eastern Zagros (Fars area), thickening of the Dalan Formation corresponds to a Mid‐Late Permian depocentre referred to here as the Permian Fars Basin. As a result of sea level fall, this depocentre evolved into a hypersaline lagoon with evaporite deposition (Nar Member). In the Triassic, the depocentre evolved into a palaeohigh as indicated by thinning and facies changes in the Kangan Formation. The results of this study draw attention to variations in the reservoir quality of the Dalan‐Kangan Formations. Much of this variation was due to the influence of the Qatar‐Fars Arch.